Functions, tasks and roles of national libraries in the 21st century. Issue 2 (August 2016) - Stephens, Andy
This article reports on work in progress within the Standing Committee of International Federation of Library Associations and Institutions (IFLA)'s National Libraries Section to develop up-to-date IFLA guidelines for national libraries to supersede the previous published United Nations Educational, Scientific, and Cultural Organization (UNESCO) standard (Sylvestre, 1987). The article notes there is no standard or prescriptive definition for the concept of 'national library': national libraries exist in a multiplicity of forms determined not least by the size, cultural history and economic development of the country they serve. Nevertheless there has been much written on the functions of national libraries and the literature in this area is reviewed. Thus, the Standing Committee agreed that it would be inappropriate to seek to develop updated guidelines or standards for national libraries that would be prescriptive : rather, it was thought that the adoption of an empirical approach, providing a wide range of exemplars and case studies of actual national library practice, would provide the national library community with a useful development toolkit. An initial pilot study to collate exemplars/case studies from 12 participating national libraries was undertaken in spring 2015. The output of the pilot study tabulated in an annex to this article constitutes an indicative inventory of national library best practice case studies, and for this reason it was thought that its wider dissemination here would be of professional interest. Finally the article reports on the next steps currently being undertaken via an online survey to document comprehensively and at a high level of granularity the functions currently being undertaken by national libraries.